Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1177/000313480807401017
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Gastric Bypass at a Large Academic Medical Center: Lessons Learned from the First 1000 Cases

Abstract: Bariatric surgery is an effective and durable treatment for morbid obesity in properly selected patients. Surgical outcomes and patient management methods should routinely be reviewed to improve patient care and maintain long-term effectiveness of the bariatric operation. Over a 5-year period, 1096 laparoscopic Roux-en-Y gastric bypass operations were performed at our institution. A comprehensive prospective database was maintained, which included data for comorbidities, operative techniques, perioperative man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Patients who had LRYGB (January 2003 to December 2008) at a single program were consecutively identified from an existing database. 4 One hundred and ninetyseven patients with at least 1 year follow-up who had agreed to be contacted for research were invited by email to participate in a retrospective survey. One hundred and forty-eight (75%) patients completed surveys.…”
Section: Methodsmentioning
confidence: 99%
“…Patients who had LRYGB (January 2003 to December 2008) at a single program were consecutively identified from an existing database. 4 One hundred and ninetyseven patients with at least 1 year follow-up who had agreed to be contacted for research were invited by email to participate in a retrospective survey. One hundred and forty-eight (75%) patients completed surveys.…”
Section: Methodsmentioning
confidence: 99%
“…However, there have been some researchers who have found that psychosocial improvements only last for the first couple of years after surgery (Greenberg, Smith, & Rockhart, ). Furthermore, other investigators have found that after surgery, some clients experience distress related to the behavioral adjustments required after surgery (Tejirian, Jensen, Lewis, Dutson, & Mehran, ), develop eating disorders (Bonne, Bashi, & Berry, ; Kalarchian et al., ), experience an increase in high risk‐taking behaviors (Vazzana, ), or experience what some have referred to as the “addictions transfer phenomenon” (Marcus, Kalarchian, & Courcoulas, ; Sarwer et al., ). Sarwer et al.…”
Section: Impact Of Obesity On the Patientmentioning
confidence: 99%
“…Tejirian et al 18 reported the experience of 4 surgeons with 1096 gastric bypass procedures over a 5-year period. They, too, modified their technique as their experience progressed and reported an overall complication rate of 7%.…”
Section: Discussionmentioning
confidence: 99%